From the Neue Gemeinschaft to Bar Kochba: The Jewish Communitas or the Idea of Jewish Politics as Mysticism - Engel, Amir 1974- (2022)
This essay uses both published and archival material to reconstruct the ideological and social contexts of Martin Buber’s 1909 address “Judaism and the Jews”. It suggests that Buber’s address became immensely influential because it equated mysticism and politics into one metaphor. Secondly, it shows that Buber imported this idea from debates and discussions that took place almost a decade earlier in Berlin, among the bohemian circle known as the Neue Gemeinschaft (new community). Finally, the author hopes to show that the social context can be as crucial to understanding an idea as the ideological context. The question about the functions and potentials of the “community” so central to Buber and the Neue Gemeinschaft must be examined, this essay contends, not only conceptually but also as a lived reality. In order to get a glimpse of “the new community”, this essay reproduces archival material that testifies not only to what people thought but also what they did, who they were, and how they interacted.
Keywords: Anarchism; Gustav Landauer; German Jewish culture; Zionism; utopism; avant-garde; die Neue Gemeinschaft; Communitas; Martin Buber